Analgesics Self-Medication and Its Effects on Sleep Quality: Among Medical Students in Peshawar. - Muhammad, Taj; Zohaib, Hafiz Muhammad; Zeb, Iqra; Gul, Saira; Shadab Mian, Muhammad; Falah, Shaikh Fahad (Journal of Neonatal Surgery, 2025)
Background: Medical students are commonly seen engaging in self-medication with analgesics due to the pressure and load of studies, availability of medicines, knowledge of common medicines and avoidance of seeking medical help for minor symptoms. Analgesic medication can help alleviate headache, body pain, fever, menstrual pain and stress-related pain but unsupervised use can lead to inappropriate use of medication and can be indicative of lifestyle or health related issues. Poor sleep may also impair concentration, memory, academic achievement, mood, and overall health, which are other issues that medical students want to focus on. Objective: To determine the frequency of analgesic self-medication and assess its association with sleep quality among medical students in Peshawar. Methods: The study was of a cross sectional design conducted in four medical colleges located in public and private sector of Peshawar (two public and two private sector medical colleges) and included undergraduate medical students. There were a total of 404 medical students included. Structured self-administered questionnaire was used to gather data. Analgesic self-medication was defined as past month use of analgesics without a prescription from a doctor. Sleep quality was assessed as very good, fairly good, fairly bad, very bad. The frequencies and percentages were computed and Chi square test used for analyzing Data. Statistically significant was defined as a p-value of ≤0.05. Results: Out of 404 students, 238 (58.9%) reported using analgesics without a medical prescription during the past month, while 166 (41.1%) did not report analgesic self-medication. Among students who practiced analgesic self-medication, 59 (24.8%) reported very good sleep quality, 125 (52.5%) fairly good, 35 (14.7%) fairly bad, and 19 (8.0%) very bad sleep quality. Among non-users, 52 (31.3%) reported very good sleep quality, 75 (45.2%) fairly good, 27 (16.3%) fairly bad, and 12 (7.2%) very bad sleep quality. The association between analgesic self-medication and sleep quality was statistically non-significant (p = 0.422). Conclusion: Analgesic self-medication was common among medical students in Peshawar; however, it was not significantly associated with sleep quality. The findings suggest that sleep quality among medical students may be influenced by other academic, psychological, and lifestyle-related factors. Awareness regarding rational analgesic use and healthy sleep practices should be promoted among medical students.